UPAYA MENINGKATKAN HASIL BELAJAR KOGNITIF SENI TARI DENGAN MENERAPKAN STRATEGI PEMBELAJARAN AKTIF TIPE CROSSWORD PUZZLE - Serli, Serli; Istiandini, Winda; Djau, Nurmila Sari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this study in class XI IPS 2 Pontianak SMA 4 students was still low level of cognitive understanding; in addition students lacked participation in learning, it caused learning results were less meaningful for students. The learning process of dance still used conventional methods.This reasarch was purpose to describe a concept, implementation, and increase of cognitive study research by dance art with active learning the kind of Crossword Puzzle at XI IPS 2 of SMA 4 Pontianak. This research with kind of action research (PTK) with of two cycles. The technique of all data that used was observations, test, documentation. This research showed increase of pra cycles result with previous learning around 6,67%, after the first cycle learning with result become 63,3% and the second cycle will be 80%.This action active learning strategy with kind of Crossword Puzzle could describe a concept, implementation, and also increase the result of cognitive learning with dance art.Keyword: The result of cognitive leaerning, Dance art Learning, Crossword Puzzle